Critical blow-up exponents for a nonlocal reaction-diffusion equation with nonlocal source and interior absorption - Zheng, Jiashan (Nonlinear Analysis: Modelling and Control, 2016)
This paper is concerned with a nonlocal reaction-diffusion equation with the nonlocal source and interior absorption with Dirichlet conditions or Neumann conditions. We investigate the critical blow-up exponents of the problem by constructing adequate supersolutions and subsolutions. Moreover, we show that the blowup rate is the same as the corresponding ODE under the appropriate hypotheses.
Keywords: nonlocal reaction-diffusion; blow-up rate; critical exponents